Structural basis of phosphatidylcholine recognition by the C2–domain of cytosolic phospholipase A2α - Yoshinori Hirano; Yong-Guang Gao; Daniel J Stephenson; Ngoc T Vu; Lucy Malinina; Dhirendra K Simanshu; Charles E Chalfant; Dinshaw J Patel; Rhoderick E Brown (eLife, 2019)
Ca2+-stimulated translocation of cytosolic phospholipase A2α (cPLA2α) to the Golgi induces arachidonic acid production, the rate-limiting step in pro-inflammatory eicosanoid synthesis. Structural insights into the cPLA2α preference for phosphatidylcholine (PC)-enriched membranes have remained elusive. Here, we report the structure of the cPLA2α C2-domain (at 2.2 Å resolution), which contains bound 1,2-dihexanoyl-sn-glycero-3-phosphocholine (DHPC) and Ca2+ ions. Two Ca2+ are complexed at previously reported locations in the lipid-free C2-domain. One of these Ca2+ions, along with a third Ca2+, bridges the C2-domain to the DHPC phosphate group, which also interacts with Asn65. Tyr96 plays a key role in lipid headgroup recognition via cation–π interaction with the PC trimethylammonium group. Mutagenesis analyses confirm that Tyr96 and Asn65 function in PC binding selectivity by the C2-domain and in the regulation of cPLA2α activity. The DHPC-binding mode of the cPLA2α C2-domain, which differs from phosphatidylserine or phosphatidylinositol 4,5-bisphosphate binding by other C2-domains, expands and deepens knowledge of the lipid-binding mechanisms mediated by C2-domains.